"Molecular rulers" for calibrating phenotypic effects of telomere imbalance. Issue 10 (1st October 2002) - Martin, C L; Waggoner, D J; Wong, A; Uhrig, S; Roseberry, J A; Hedrick, J F; Pack, S D; Russell, K; Zackai, E; Dobyns, W B; Ledbetter, D H
Abstract : As a result of the increasing use of genome wide telomere screening, it has become evident that a significant proportion of people with idiopathic mental retardation have subtle abnormalities involving the telomeres of human chromosomes. However, during the course of these studies, there have also been telomeric imbalances identified in normal people that are not associated with any apparent phenotype. We have begun to scrutinise cases from both of these groups by determining the extent of the duplication or deletion associated with the imbalance. Five cases were examined where the telomere rearrangement resulted in trisomy for the 16p telomere. The size of the trisomic segment ranged from ∼4-7 Mb and the phenotype included mental and growth retardation, brain malformations, heart defects, cleft palate, pancreatic insufficiency, genitourinary abnormalities, and dysmorphic features. Three cases with telomeric deletions without apparent phenotypic effects were also examined, one from 10q and two from 17p. All three deletions were inherited from a phenotypically normal parent carrying the same deletion, thus without apparent phenotypic effect. The largest deletion among these cases was ∼600 kb on 17p. Similar studies are necessary for all telomeric regions to differentiate between those telomeric rearrangements that are pathogenic and those that are benign variants. Towards this goal, we are developing "molecular rulers" that incorporate multiple clones at each telomere that span the most distal 5 Mb region. While telomere screening has enabled the identification of telomere rearrangements, the use of molecular rulers will allow better phenotype prediction and prognosis related to these findings.